2008
DOI: 10.12968/bjcn.2008.13.sup6.31843
|View full text |Cite
|
Sign up to set email alerts
|

Problems encountered managing pressure ulceration of the sacrum

Abstract: Pressure ulcers cause a great deal of distress, loss of dignity for the patient and can be problematic in terms of management. Pressure ulceration in the sacral area may lead to added complications if the patient has problems with urinary and faecal incontinence. Maintenance of the patient’s skin integrity is vital to avoid added discomfort and distress due to moisture lesions. Prevention of wound and dressing contamination with urine and faeces is difficult and can lead to increases in clinical risk (infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Pressure injuries can affect the patient's mobility, nutritional intake, psychological status and elimination can become problematic and prolong their length of hospital stay (3). Pressure injuries consume resources in the form of wound management, increased nursing care, physiotherapy, medications, nutritional support and other clinical services (4).…”
Section: Introductionmentioning
confidence: 99%
“…Pressure injuries can affect the patient's mobility, nutritional intake, psychological status and elimination can become problematic and prolong their length of hospital stay (3). Pressure injuries consume resources in the form of wound management, increased nursing care, physiotherapy, medications, nutritional support and other clinical services (4).…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence clearly identifies specific patient characteristics that increase the risk of PI development in the ED . Broadly, any patient who is unable to effectively reposition is at risk; similarly, patients exposed to prolonged moisture at the skin‐surface interface because of incontinence are also at risk . An important issue for the ED clinician to consider is that of the time prior to the patient's admission to the ED.…”
Section: Specific Patient Groups Who Are At High Risk Of Developing Pmentioning
confidence: 99%
“…Raised body temperature increases metabolic demands and has been associated with decreased tissue tolerance to mechanical loads. Poor nutritional status has been linked to increased PI risk because of decreased tissue tolerance and decreased fat and muscle mass over bony prominences such as the sacrum, which intensifies soft tissue deformations …”
Section: Specific Patient Groups Who Are At High Risk Of Developing Pmentioning
confidence: 99%
“…Skin integrity is optimized in the pH of 4-6.8. 8 Studies have shown that the majority of hospital-acquired pressure injuries had an emergency stay of more than 2 hours. 9,10 This study emphasizes the role of preventative measures starting from emergency department admissions.…”
Section: Review Of the Classification And Risk Factorsmentioning
confidence: 99%